2017
DOI: 10.1038/s41467-017-02245-1
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PBRM1 rescues VHL dependent replication stress to promote renal carcinogenesis

Abstract: Inactivation of the VHL (Von Hippel Lindau) tumour suppressor has long been recognised as necessary for the pathogenesis of clear cell renal cancer (ccRCC); however, the molecular mechanisms underlying transformation and the requirement for additional genetic hits remain unclear. Here, we show that loss of VHL alone results in DNA replication stress and damage accumulation, effects that constrain cellular growth and transformation. By contrast, concomitant loss of the chromatin remodelling factor PBRM1 (mutate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 55 publications
5
61
0
1
Order By: Relevance
“…A role for PBRM1 in stress response is in agreement with recent findings that PBRM1 deletion alone is not sufficient for transformation but acts to facilitate oncogenesis in cooperation with VHL deletion (Espana-Agusti et al, 2017;Gu et al, 2017;Nargund et al, 2017). PBRM1 deletion allows for an amplification of oncogenic signaling (Gao et al, 2017;Nargund et al, 2017), as well as a bypass of checkpoints induced by replication stress after VHL deletion (Espana-Agusti et al, 2017). This could be in part due to PBRM1's role in regulating the hypoxia stress response in cooperation with HIF1a, which allows for the reduction of ROS and induction of apoptosis in response to hypoxia (Kim et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A role for PBRM1 in stress response is in agreement with recent findings that PBRM1 deletion alone is not sufficient for transformation but acts to facilitate oncogenesis in cooperation with VHL deletion (Espana-Agusti et al, 2017;Gu et al, 2017;Nargund et al, 2017). PBRM1 deletion allows for an amplification of oncogenic signaling (Gao et al, 2017;Nargund et al, 2017), as well as a bypass of checkpoints induced by replication stress after VHL deletion (Espana-Agusti et al, 2017). This could be in part due to PBRM1's role in regulating the hypoxia stress response in cooperation with HIF1a, which allows for the reduction of ROS and induction of apoptosis in response to hypoxia (Kim et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Transcriptional profiling of human ccRCC indicate that PBRM1 mutant tumors have a hypoxic transcriptional signature (Sato et al, 2013), which is in agreement with recent reports that PBRM1 mutation amplifies the hypoxia inducible factor (HIF) transcriptional program signature induced upon von Hippel-Lindau (VHL) deletion in cell culture (Gao et al, 2017) and in a mouse model of renal cancer (Nargund et al, 2017). Recent work with kidney specific (KSP and PAX8) Cre mouse models indicate that VHL knockout or PBRM1 knockout alone is not sufficient for cancer formation but that both are required for kidney tumor formation in mice (Espana-Agusti et al, 2017;Gu et al, 2017;Nargund et al, 2017).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…To evaluate the pattern of nuclear distribution and intensity of H3K9me3 mark in C9BAC and control astrocytes, we used immunostaining with a widely used commercial antibody against this modification [38][39][40]. Additionally, we tested the specificity of the H3K9me3 staining in N2A cells treated with chaetocin, a pharmacological inhibitor of H3K9 methyltransferase SUV39H1/2.…”
Section: Reduced Levels Of Nuclear H3k9me3 In Primary Spinal Cord Astmentioning
confidence: 99%
“…In a mouse model, a combination of Vhl −/− and Bap1 +− deficiency in nephron progenitor cells resulted in multiple renal cysts and tumours (similar to kidneys in VHL disease) whereas Vhl −/− mice did not develop cRCC [32]. Similarly, in cellular and mouse models, loss of PBRM1/Pbrm1 in addition to VHL/Vhl was oncogenic [33][34][35]. In a seminal study, Mitchell et al [36‱‱] reported that the most frequent cause of chromosome 3p loss in cRCC is a chromothrypsis-associated rearrangement between 3p and 5q that resulted in loss of 3p and gain of 5q.…”
Section: Mechanisms Of Tumourigenesis In Vhl Disease and Sporadic Vhlmentioning
confidence: 98%